Reasons for missing clinically significant prostate cancer by targeted magnetic resonance imaging/ultrasound fusion-guided biopsy. Issue 137 (April 2021) - Klingebiel, M.; Arsov, C.; Ullrich, T.; Quentin, M.; Al-Monajjed, R.; Mally, D.; Sawicki, L.M.; Hiester, A.; Esposito, I.; Albers, P.; Antoch, G.; Schimmöller, L.
Highlights: MRI-targeted biopsy (TB) can miss MRI cancer suspicious regions (mCSR) and csPCA. Main reasons missing csPCa were insufficient segmentation or imprecise registration within MRI/US fusion-guided biopsy. Pre-biopsy verification of MRI quality, correct segmentation and registration, and clinical experience seems essential. Abstract: Objectives: This study evaluates cases with clinically significant prostate cancer (csPCa) missed by targeted biopsy (TB) and analyzes the diagnostic impact of an additional systematic biopsy (SB) in a large patient collective. Methods: Consecutive patients with a 3 T multiparametric prostate MRI (mpMRI) and a subsequent MRI/US fusion-guided TB plus 12-core US-guided SB from 01/2014 to 04/2019 were included in this study. Primary study endpoint was the analysis of cases with a csPCa missed by TB and detected by SB. Secondary study objectives were the PCa detection and the correlation with clinical and MRI parameters. Results: In total 785 patients met the inclusion criteria. 342 patients had a csPCa (median PSAD 0.29 ng/mL/cm 3 ). In 42 patients (13 %), a csPCa was detected only by SB. In 36 of these cases, the localization of the positive SB cores matched with the cancer suspicious region described on mpMRI (mCSR). Cases with a csPCA missed by TB showed either an insufficient MRI segmentation (prostate boundary correlation) (31 %) and/or insufficient lesion registration (lesion transfer, tracking, and/or matching) (48 %), a missed small lesion (14 %), or a failed center of a large lesion (10 %). Median PSAD of patients with non-significant PCa detected by SB was 0.15 ng/mL/cm 3 . Conclusions: Main reasons for missing a csPCa by TB were insufficient prostate segmentation or imprecise lesion registration within MRI/US fusion-guided biopsy. Consequently, verification of MRI quality, exact mCSR assessment, and advanced biopsy experience may improve accuracy. Altogether, an additional SB adds limited clinical benefit in men with PSAD ≤ 0.15 ng/mL/cm 3 .